A diagnostic expert system to overcome construction problems in rigid highway pavement - Mosa, Ahmed Mancy; Taha, Mohd Raihan; Ismail, Amiruddin; Rahmat, Riza Atiq O. K. (Journal of Civil Engineering and Management, 2013)
Constructing highway pavements faces complex problems, which are affected by multiple factors, where solution is nearly impossible without expert assistance. Diagnosing such construction problems and suggesting most suitable cost efficient solutions requires significant engineering expertise, which might not be available in all construction sites due to inadequate resource and remote locations. Developing an expert system in this domain is a very effective way to help novice engineers to overcome these problems and to learn about them. Moreover, the system can be used as an archive to document engineering knowledge and to share expertise among the experts in this domain. This article describes the development and evaluation stages of such a system, including knowledge acquisition, knowledge representation, system building, and system verification and validation. The initial knowledge is acquired from literature reviews. More expert knowledge is elicited through interviews and questionnaires. This knowledge is documented, analyzed, represented, and converted to computer software using the Visual Basic programming language and the system is called ES-CCPRHP. The system has been verified and validated in three ways: by extensive testing, comparison between system performance and expert reasoning, and case study. It can therefore be employed with confidence by end users. First published online: 24 Oct 2013